Using low cost components to determine chlorophyll concentration by measuring fluorescence intensity - Truter, Johannes Petrus (Department of Electrical Engineering, 2017)
This dissertation describes the development of a low cost fluorometer with the aim of using it as an algae and phytoplankton concentration sensor. As it forms the core of this fluorometer's functionality, chlorophyll's fluorescence characteristics and origins are discussed. Special attention is given to the variability of chlorophyll fluorescence as it has a big influence on measurements. Experimental procedures and data are provided to show why each component was finally selected for use in the fluorometer. An analogue front end device with programmable gain on each 24-bit ADC channel forms the interface between the high sensitivity TSL257 light-to-voltage light sensors and the 32-bit ARM microcontroller that controls the system. The microcontroller software controls the 470 nm LED current to create a 75 ms light pulse that has a 63 Hz sine wave modulated on it. The low cost light sensors proved to be sensitive enough to detect the low light intensities of chlorophyll fluorescence. The challenges of measuring the low level voltages from these light sensors are discussed. The amount of noise on the light sensor voltages at low chlorophyll concentrations make it difficult to accurately measure the fluorescence signal. Different light modulation and digital signal processing techniques were investigated to compare the effective recovery of the fluorescence signal. Sine wave modulation along with sample averaging provided good results. The results of laboratory experiments with pure chlorophyll α and extracted chlorophyll are discussed to give an overview of the capabilities and limitations of the developed fluorometer that is able to measure the fluorescent light from extracted chlorophyll concentrations as low as 0.01 μg/1.